2014
DOI: 10.1136/bmjopen-2014-005632
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption and risk of type 2 diabetes mellitus: a systematic review and meta-analysis update

Abstract: ObjectiveTea has been suggested to decrease blood glucose levels and protect pancreatic β cells in diabetic mice. However, human epidemiological studies showed inconsistent results for the association between tea consumption and type 2 diabetes mellitus (T2DM) risk. The aim of this study was to conduct a meta-analysis to further explore the association between tea consumption and incidence of T2DM.DesignSystematic review and meta-analysis.MethodsWe performed a systematic literature search up to 30 August 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 50 publications
2
56
1
Order By: Relevance
“…A cohort study of oolong tea consumption also suggested that consuming either one or two cups of oolong tea per day had a significant linear and inverse correlation incident rate of type 2 diabetes (Hayashino, Fukuhara, Okamura, Tanaka, & Ueshima, 2011). A study suggested that a daily tea consumption (≥3 or ≥4 cups/day) is associated with a lower T2DM risk, but some clinical trials show that the risk of T2DM has no significant relationship with tea consumption (Jing et al, 2009;Yang, Mao, Xu, Ma, & Zeng, 2014). More clinical trials should be conducted to assess the effects of tea consumption on T2DM.…”
Section: Antidiabetes Effectmentioning
confidence: 99%
“…A cohort study of oolong tea consumption also suggested that consuming either one or two cups of oolong tea per day had a significant linear and inverse correlation incident rate of type 2 diabetes (Hayashino, Fukuhara, Okamura, Tanaka, & Ueshima, 2011). A study suggested that a daily tea consumption (≥3 or ≥4 cups/day) is associated with a lower T2DM risk, but some clinical trials show that the risk of T2DM has no significant relationship with tea consumption (Jing et al, 2009;Yang, Mao, Xu, Ma, & Zeng, 2014). More clinical trials should be conducted to assess the effects of tea consumption on T2DM.…”
Section: Antidiabetes Effectmentioning
confidence: 99%
“…Regular consumption of tea is also associated with reduced risk of developing type 2 diabetes in meta‐analyses (Yang et al . , ; Fig. ).…”
Section: Human Intervention Studies On Flavanols and Flavanol‐rich Fomentioning
confidence: 94%
“…Data on tea are supported by the meta‐analysis reported by Yang et al . (). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Human Intervention Studies On Flavanols and Flavanol‐rich Fomentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding tea intake, several meta-analyses also reported potential beneficial effects, although it is not clear whether they are in a dose-response manner [47,48,49,50]. These beneficious effects on T2DM include an association with decreased IR [50,51], but not with increased insulin secretion and postprandial effects rather than in fasting glucose metabolism [52,53].…”
Section: Effects Of Nutrients On Gene Expression In the Pathogenesmentioning
confidence: 99%